Anomalies detection in adhesive wall tiling systems by infrared thermography - Lourenço, Tomás (2018)
Adherent tiling systems are widely used all over the world as wall cladding because of their aesthetic and technical characteristics. However, anomalous behaviours often occur; compromising the overall behaviour of facades, and possibly raising safety risks. The need to create expeditious, non-destructive and accurate methods of inspection that can encourage these systems’ inspection and maintenance fomented a research study on infrared thermography’s capacity of early detect anomalous zones in adhesive tiling systems, such as detachments or presence of humidity, in controlled in situ conditions, proving it as a valuable diagnostic tool.